A Mother’s Choice: Undocumented motherhood, waiting and smuggling in the Tunisian–Libyan borderlands - Chemlali, Ahlam (Trends in organized crime, 2023)
Anecdotal evidence suggests growing numbers of migrants intercepted at sea – referred to by the Tunisian coastguard as les rescapés (the rescued) – return to Libya via smuggling. In this article I empirically document the experiences of “rescued” migrant mothers who consider and/or purposely re-engage in irregular, high-risk returns involving crossing the Tunisian border back into Libya. Employing a feminist ethnographic approach, this paper explores how undocumented motherhood is experienced and shaped in the context of EU-sponsored counter-smuggling and border enforcement. Building on fieldwork in Medénine, in southern Tunisia, I also examine the considerations of migrant mothers “stuck on the move” concerning clandestine navigation and redirection in the complicated temporal and spatial context created by international organizations and EU-sponsored forms of “protection.” I argue that border enforcement and counter-smuggling policies not only impact everyday life and mobility for undocumented mothers and their children but, as gendered practices, also trap and confine migrant mothers and their children in a cycle of protracted vulnerability, indefinite waiting, and uncertainty in which opting to travel with smugglers becomes the best bet and last resort.